Embracing the Chaotic: Cynefin and Humanitarian Response - and Morealtitude (2010)
Note: Many thanks to Dave Snowden for his willingness to comment on this article prior to release Because I’m always a little behind the eight-ball, a friend of mine* recently introduced me to the …